ANALISIS USER EXPERIENCE PADA PLATFORM LINKEDIN MENGGUNAKAN METODE USER EXPERIENCE QUESTIONNAIRE - Indriyana, Siti; Muthmainah, Tasyifa Nafsiah; Ridha, Azhari Ali (Universitas Methodist Indonesia, 2023)
LinkedIn is the largest professional networking application in the world, classified as a social networking site (SNS) application. Indonesia is one of the countries with the highest number of active LinkedIn users. To ensure user comfort, LinkedIn regularly updates their application. However, recently there have been some negative ratings regarding the LinkedIn application. To directly assess this, a research study was conducted to determine user satisfaction while interacting with the features available on LinkedIn. This research was carried out using the user experience questionnaire method, with 35 respondents participating. This method consists of 26 questions representing six assessment indicators, including attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty. The indicator with the highest score is stimulation, with a score of 1.48, which is categorized as good. On the other hand, the lowest indicator score is perspicuity, which only obtained a score of 0.79, below average. Overall, LinkedIn has received predominantly positive feedback. However, it is still recommended to continue innovating, especially focusing on improving perspicuity aspects that are tailored to the needs and issues faced by users.